Implications of a Philippine-US free trade agreement on trade in goods: An indicator approach - George Manzano; Kristine Joy Martin (Philippine Institute for Development Studies (PIDS), 2014)
The Trans-Pacific Partnership (TPP) is a regional free trade agreement (FTA) initiated by the United States (US) and is presently being negotiated among 11 countries. With the Philippines negotiating in many fronts at the global scene, such as its engagement in the ASEAN Economic Community and in the forthcoming European Union-Philippine FTA, among others, the invitation to join the TPP is another opportunity worth studying. Departing from the prevalence of computable general equilibrium models in estimating the effects of the TPP on prospective partners, this study will use an alternative methodology, the Sussex framework. It aims to complement the existing works of other researchers in the field. This paper furthermore will focus on analyzing the (1) possible impact on Philippine-US trade in goods in joining the TPP agreement as well as the (2) probable negative effects that could befall the country if it were not a member of the TPP once the agreement is completed. More specifically, to analyze the impact of the TPP on Philippine-US trade in goods, the study will model the TPP as a collection of bilateral US-TPP partner FTAs. The relevant indicators generated from the series of bilateral FTAs will then be interpreted in the context of how these would impact on the Philippines as a third, nonpartner country.
Keywords: 330; Philippines; free trade agreements (FTAs); Trans-Pacific Partnership; Philippine-US trade; Sussex framework; TPP